Prediction of future great earthquake times off Kamchatka and the northern Kurils - Vikulin A.V. (1993)
On the basis of the writer's data of the migration of great 18-20th century earthquakes and their repeat times he offers a forecast of the times of large earthquakes that are likely to occur in the northern Kurils and Kamchatka during the late 20th - early 21st centuries. The evolution of a seismicity pattern in the region is suggested.